Identifying factors for poorer educational outcomes that may be exacerbated by COVID‐19: A systematic review focussing on at‐risk school children and adolescents. Issue 1 (19th September 2022) - Coles, Laetitia; Johnstone, Melissa; Pattinson, Cassandra; Thorpe, Karen; Van Halen, Olivia; Zheng, Zhaoxi; Bayliss, Olivia; Lakeman, Nicole; Western, Mark; Povey, Jenny; Staton, Sally
Abstract: School closures across Australia in response to COVID‐19 have persisted since 2020, with rising mental health problems in children and adolescents, alongside rising negative family health and socioeconomic outcomes. Further, some children and young people who were already experiencing disadvantage pre‐pandemic may be at heightened risk of poorer educational outcomes. Therefore, the aim of this study was to conduct a systematic review of the literature to identify the factors for poorer educational outcomes that may be exacerbated by COVID‐19 amongst disadvantaged school students. Key development stages of disadvantage were identified: young children who started school behind, older students already at risk of disengagement from school and children and young people who have had contact with the child protection system. Five databases were systematically searched, across two search periods. A total of 69 Australian, peer‐reviewed articles, published in 2005–2021, examining risk factors for poor educational outcomes for children attending school met the inclusion criteria and were included in final analyses. Our findings provide evidence of key risk factors that make these populations susceptible to worsening outcomes resulting from the COVID‐19 pandemic, and of the critical importance of ongoing research to guide policy and practice support for these at‐risk groups.